PENGARUH SIKAP BELAJAR TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN BIOLOGI KELAS XI SMA NEGERI 3 MERANGIN TAHUN PELAJARAN 2017/2018 - Andriyanto (Pendidikan Matematika | STKIP YM Bangko, 2019)
Purpose of this study is: To find out is there a significant effect of learning attitudes towards Biology learning outcomes of students of Class XI SMA Negeri 3 Merangin 2017/2018 Academic Year. The research approach that will be used in this study is a quantitative approach, while the correlational quantitative method. The correlational quantitative method is used because this study seeks to find whether there is an influence between learning attitudes towards Biology learning outcomes of students of Class XI SMA Negeri 3 Merangin 2017/2018 Academic Year. This type of research is quantitative research with experimental methods. The population in this study were all 11th grade students of SMA Negeri 3 Merangin 2017/2018 Academic Year. Learning attitudes have a relationship of 0.727 to the learning outcomes of biology subjects in Class XI SMA Negeri 3 Merangin 2017/2018 Academic Year. Based on the significance test obtained value t_ (count =) 5,459 and by taking α = 0.05 and n = 48 one-party test then: dk = n - 2, 48 - 2 = 46 so that the value t_ (table =) = 2,0129 , then there is a significant effect between learning attitudes towards Biology student learning outcomes of students of Class XI SMA Negeri 3 Merangin 2017/2018 Academic Year. While the calculation of the Determinant Coefficient (KP) is 39.313%. This shows that 39.313% of learning outcomes are influenced by learning attitudes and the remaining 60.6871% is influenced by other factors. So that it can be concluded that Ho is rejected, which means that there is a significant effect between learning attitudes and learning outcomes of biology subjects in Class XI students of SMA 3 Merangin 2017/2018 Academic Year. Keywords: learning attitude, learning outcomes, biology